2019
DOI: 10.1039/c9ra07325f
|View full text |Cite|
|
Sign up to set email alerts
|

Toward realistic computer modeling of paraffin-based composite materials: critical assessment of atomic-scale models of paraffins

Abstract: Atomic-scale computational models of paraffins are critically assessed and compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 90 publications
4
33
0
Order By: Relevance
“…It is to be noted that even for such a long simulation, the standard error is up to 10%. This magnitude of deviation has also been reported by Glova et al 30 Zhang et al 54 proposed to use a large number of shortindependent simulation runs to improve the reliability of viscosity.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…It is to be noted that even for such a long simulation, the standard error is up to 10%. This magnitude of deviation has also been reported by Glova et al 30 Zhang et al 54 proposed to use a large number of shortindependent simulation runs to improve the reliability of viscosity.…”
Section: Resultssupporting
confidence: 77%
“…27 The decane and eicosane molecules are described with a united atom model, the transferable potential for the phase equilibria (TraPPE) model. 28,29 We chose this model, as Glova et al 30 reported a good agreement of this model's results with experimental results. This model treats each CH 3 and CH 2 group as a pseudoatom having a single interaction center, and the pseudoatoms are connected using harmonic C−C bond, C−C−C angle, and C−C−C−C dihedral potentials.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Allatom model oplsaa is used to describe the interaction between alkanes. 66,67 This force field can help to characterize thermophysical properties of PCM, such as density, melting temperature and specific heat capacity more accurately. 51 The functional form of the oplsaa force field potential is shown as:…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The PCM used in this paper is n ‐Hexadecane. All‐atom model oplsaa is used to describe the interaction between alkanes 66,67 . This force field can help to characterize thermophysical properties of PCM, such as density, melting temperature and specific heat capacity more accurately 51 .…”
Section: Thermophylic Properties Of Pcm Under Different Pressuresmentioning
confidence: 99%
“…The results lead to the suggestion that for long-chained alkanes the all-atom OPLS force field for long hydrocarbons, L-OPLS-AA, should be used. Glova et al [10] gives a detailed study comparing in total 10 all-atom and united-atom force fields. They simulated an Eicosane system and computed thermal, structural and dynamic properties such as the density, viscosity and crystal structure.…”
Section: Introductionmentioning
confidence: 99%